2007
DOI: 10.1007/bf03022031
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of tramadol on vasorelaxation mediated by ATP-sensitive K+ channels in rat aorta

Abstract: Purpose: Tramadol produces a conduction block similar to lidocaine by exerting a local anesthetic-like effect. The aims of this in vitro study were to determine the effects of tramadol on the vasorelaxant response induced by the adenosine triphosphate-sensitive K + (K ATP ) channel opener, levcromakalim, in an endothelium-denuded rat aorta, and to determine whether this effect of tramadol is stereoselective. Methods:The effects of tramadol (racemic, R(-) and S(+): 10 -6 , 10 -5 , 5 × 10 -5 M), and glibenclamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, it may also be a regulator of ion channels. As examples, it inhibits 5-HT-induced Ca 2+ -activated-Cl − current [5], delayed rectifier K + current [6], and a supraclinical dose attenuates the vasorelaxation mediated by the K ATP channels in the rat aorta [7]. Although the analgesic effects of tramadol are thought to result from the sum of these, the detailed mechanisms have not yet been completely clarified.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, it may also be a regulator of ion channels. As examples, it inhibits 5-HT-induced Ca 2+ -activated-Cl − current [5], delayed rectifier K + current [6], and a supraclinical dose attenuates the vasorelaxation mediated by the K ATP channels in the rat aorta [7]. Although the analgesic effects of tramadol are thought to result from the sum of these, the detailed mechanisms have not yet been completely clarified.…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, Kaya et al 25 showed that ATPsensitive and Ca 2+ -activated K + channels are not involved in the vasodilator action of tramadol in rabbit isolated aorta. Conversely, Cho et al 26 demonstrated that tramadol attenuates vasorelaxant responses to ATP-sensitive K + channel activation in normotensive rat aorta.…”
Section: Discussionmentioning
confidence: 95%